Ambient N2 fixation to NH3 at ambient conditions: Using Nb2O5 nanofiber as a high-performance electrocatalyst. (October 2018) - Han, Jingrui; Liu, Zaichun; Ma, Yongjun; Cui, Guanwei; Xie, Fengyu; Wang, Faxing; Wu, Yuping; Gao, Shuyan; Xu, Yuanhong; Sun, Xuping
Abstract: Electrochemical reduction has emerged as an environmentally-benign and sustainable approach alternative to the Haber–Bosch process for artificial N2 fixation at ambient conditions, while the challenge associated with N2 activation underlines the demand of efficient electrocatalysts for the N2 reduction reaction (NRR). In this work, Nb2 O5 nanofiber is experimentally proved to act as a non-noble-metal NRR electrocatalyst for N2 conversion to NH3 with high activity and selectivity. When tested in 0.1 M HCl, such Nb2 O5 nanofiber achieves a high average NH3 yield (43.6 µg h −1 mg −1 cat. ) and a high Faradaic efficiency (9.26%) at − 0.55 V vs. reversible hydrogen electrode, rivaling the performances of most reported aqueous-based NRR electrocatalysts under ambient conditions and even comparable with those under high temperature and pressure. Notably, it also shows high stability during electrolysis and recycling test. The catalytic mechanism of NRR on Nb2 O5 (181) surface is further discussed by density functional theory calculations. Graphical abstract: Nb2 O5 nanofiber acts as an efficient electrocatalyst for N2 fixation to NH3 with high electrochemical stability at ambient condition. In 0.1 M HCl, it shows high activity with a NH3 yield of 43.6 µg h –1 mg –1 cat. and a FE of 9.26% at − 0.55 V vs. reversible hydrogen electrode. fx1 Highlights: Nb2 O5 nanofiber is active for ambient electrocatalytic N2 fixation to NH3 . It achieves a large NH3 yield of 43.6 µg h −1 mg −1 cat. at − 0.55 V vs RHE. It attains a high Faradaic efficiency of 9.26% at − 0.55 V vs RHE. It shows high electrochemical stability.